Tai ping yang, da xi yang - Huang, Beijia 1955- (Huang Bei jia qing qing xiao shuo xi lie, 2024)
The Jingjiniao Choir from Nanjing is travelling to Ireland to take part in a world-class children's choir competition. On the eve of its departure from Dublin, an old overseas Chinese in his eighties shows three children in the group a brass trumpet mouthpiece that he had planned to give to his friends seventy years ago. A story spanning time begins... - Huang Beijia, born in Rugao, Jiangsu, began publishing literary works in 1973. She graduated from the School of Chinese Language and Literature at Peking University in 1982. In 1984, she became a professional writer with the Jiangsu Writers Association